PREVALENCE OF THYROID DISORDERS IN HIGH-RISK PREGNANCIES AT A PUBLIC MATERNITY HOSPITAL IN THE FEDERAL DISTRICT AND ASSOCIATED COMORBIDITIES - de Meneses, Alana Pires da Silveira Fontenele; Salgado, Uanda Beatriz Pereira; Silva, Marina Teixeira de Oliveira; Pereira, Allana Laís Rocha; Santos, Leticia Nascimento; de Souza, Geovana Borges; Chater, Arthur Habib Abrão; Floriano, Riane Fernandes Gomes (Seven Editora, 2025)
Thyroid function is regulated by the hypothalamic-pituitary-thyroid axis. During pregnancy, there are various mechanisms that stimulate this axis, which can trigger or worsen maternal thyroid disorders and generate maternal-fetal repercussions. Hyperthyroidism is relatively uncommon during pregnancy, occurring in 0.1 to 0.4% of all pregnancies. Hypothyroidism, on the other hand, has a very wide geographical variation in its prevalence during pregnancy, from 2.5% to 11%, and is higher in Asian countries compared to Western countries. In view of this, this study aimed to assess the prevalence of thyroid disorders during pregnancy in a high-risk prenatal clinic at a public hospital in the Federal District during the period 2023 and 2024 and the association of this disorder with other maternal comorbidities. The results found a prevalence of thyroid disorders during pregnancy of 19.8%, of which 15.5% were hypothyroidism and 4.3% hyperthyroidism. When assessing the association between hypothyroidism and the comorbidities presented by the pregnant women, a statistically significant association was found with a diagnosis of gestational diabetes mellitus (p = 0.002), obesity (p = 0.051) and a history of thyroid cancer (p < 0.001), in addition to pregnancy itself being a risk factor for the development of thyroid disorders (p < 0.001). It was possible to conclude the importance of universal screening for thyroid disorders, given that this is a disorder with high maternal-fetal risks during pregnancy. DOI: https://doi.org/10.56238/sevened2025.021-054